(untitled) (Palimpsesto, 2017)
The main objective article develops a reflection on the modalities of expression of the social bond in the images and the aesthetic of the New Argentine Cinema. It was first proposed an introduction to the definition of that new cinema and its aesthetic and historical specificities and then linked to some theoretical indications of social and cultural transformations at the current time. It is developed a reflection that analyzes the images and narratives of the new Argentine cinema as means of expression of those cultural and social changes, which require defining a relationship between images and social experience that shows the flow of relations between individuals.